Lift enhancement by bats' dynamically changing wingspan - Wang, Shizhao; Zhang, Xing; He, Guowei; Liu, Tianshu (Journal of the Royal Society interface, 2015)
This paper elucidates the aerodynamic role of the dynamically changing wingspan in bat flight. Based on direct numerical simulations of the flow over a slow-flying bat, it is found that the dynamically changing wingspan can significantly enhance the lift. Further, an analysis of flow structures and lift decomposition reveal that the elevated vortex lift associated with the leading-edge vortices intensified by the dynamically changing wingspan considerably contributed to enhancement of the time-averaged lift. The nonlinear interaction between the dynamically changing wing and the vortical structures plays an important role in the lift enhancement of a flying bat in addition to the geometrical effect of changing the lifting-surface area in a flapping cycle. In addition, the dynamically changing wingspan leads to the higher efficiency in terms of generating lift for a given amount of the mechanical energy consumed in flight.